Early Childhood Dietary Intake and Subsequent Socioemotional and Cognitive School Readiness Among Australian Children - Hammersley, Megan L; Buchanan, Limin; Xu, Huilan; Wen, Li Ming (My University, 2022)
Dietary intake can affect the physical, cognitive, and socioemotional development of young children. Few studies have explored the relationships between dietary intake and the cognitive and socioemotional dimensions of school readiness. This study aimed to investigate the longitudinal associations between children's dietary intake in early childhood, and cognitive and socioemotional school readiness indicators at age 4-5 years using data from the Longitudinal Study of Australian Children. A total of 4,253 children were included in the analysis. Multiple linear regression models were built to investigate whether dietary intake (measured by questionnaire at parent interview) at age 2-3 years predicted school readiness indicators of socioemotional and behavioral functioning (measured by parent-reported Strengths and Difficulties Questionnaire [SDQ total score and pro-social scale]), verbal (assessed by Peabody Picture Vocabulary Test-Third Edition [PPVT-III]) and nonverbal (assessed by "Who Am I" test [WAI] cognitive skills) at age 4-5 years. Furthermore, using cross-sectional data at age 4-5 years, four multiple linear regression models were built to investigate if dietary intake was correlated with the aforementioned school readiness indicators. All models were adjusted for potential confounders. It was found that every one-point increase in child dietary intake score at age 2-3 years led to a decrease in SDQ total score by 0.19 (95% confidence interval [CI] = [0.10, 0.28], and an increase in SDQ pro-social scale, WAI score and PPVT score by 0.07 (95% CI = [0.03, 0.10]), 0.27 (95% CI = [0.13, 0.41]), and 0.20 (95% CI = [0.09, 0.30]), respectively, at age 4-5 years. Children's dietary intake was also a correlate of their school readiness at age 4-5 years. These results add to the limited evidence base suggesting that children's early dietary intake may play an important role in later socioemotional and behavioral development, and the development of cognitive skills, which are critical school readiness indicators.
Health Education & Behavior
Keywords: Childhood and child development; Health and wellbeing; Learning, education and training